FAMILY CASE OF MITRAL VALVE PROLAPSE — IMPACT OF INCREASED LEVEL OF TRANSFORMING GROWTH FACTOR β - M. Yu. Omelchenko; E. G. Malev; L. B. Mitrofanova; L. V. Vasina; E. V. Zemtsovsky; A. O. Nedoshivin (Российский кардиологический журнал)
.